Dietary patterns of herds during the Chalcolithic: Ota and its regional significance - Samarakoon, Yasasmi Sewwandi (2024)
With the neolithization, new subsistence strategies emerged across Europe, fundamentally changing human- animal interactions and resource use. During Chalcolithic period in Iberian Peninsula witnessed significant advancements in subsistence strategies, including animal husbandry practices. This study examines faunal remains from the walled settlement of Ota, located in Estremadura region in Portugal, to reconstruct dietary patterns, grazing system and livestock management strategies in Chalcolithic period. Stable isotopic analysis (δ13C and δ15N) was performed on 35 faunal bone collagen samples from domestic and wild species. The δ13C values among faunal samples indicate that animal diet was consist with C3 plants, while elevated δ13N values from domestic herds suggest grazing on fertilized fields supplemented with forge, reflecting a sophisticated approach to animal care. The similarity in δ13N values between pig and domesticated herbivores demonstrates semi-free management practice for domestic omnivores at the site. These finding highlight that intentional animal and land management practices were integral to subsistence strategies at Ota, reflecting a structured socio-economical system. Evidence points to animal management strategies over domestic herds in Ota, consistent with contemporaneous practices observed at other Chalcolithic sites in Extremadura and Alentejo regions. Furthermore, stable isotopic evidence suggests that the Ota walled settlement may have engaged with existing animal exchanging networks during 3rd millennium BCE. By providing insights into animal husbandry and its socio-economic implications, this study contributes to understanding the complex interplay between environment, subsistence strategies and societal organization in Chalcolithic Western Iberia; - Resumo: Com a neolitização, surgiram novas estratégias de subsistência em toda a Europa, transformando fundamentalmente as interações entre humanos e animais, bem como o uso de recursos. Durante o período Calcolítico, a Península Ibérica testemunhou avanços significativos nas estratégias de subsistência, incluindo práticas de criação de animais. Este estudo examina os restos faunísticos do assentamento muralhado de Ota, localizado na região da Estremadura, em Portugal, para reconstruir padrões alimentares, sistemas de pastoreio e estratégias de gestão pecuária durante o período Calcolítico. Foi realizada análise isotópica estável (δ13C e δ15N) em 35 amostras de colágeno ósseo de espécies domésticas e selvagens. Os valores de δ13C entre as amostras faunísticas indicam que a dieta animal consistia predominantemente em plantas do tipo C3, enquanto os valores elevados de nos rebanhos δ15N domésticos sugerem pastoreio em campos fertilizados suplementado com forragem, refletindo uma abordagem sofisticada aos cuidados com os animais. A semelhança nos valores de δ15N entre porcos e herbívoros domesticados demonstra práticas de gestão semi livre para onívoros domésticos no local. Estes resultados destacam que práticas intencionais de gestão animal e do solo eram parte integrante das estratégias de subsistência em Ota, refletindo um sistema socioeconómico estruturado. As evidências apontam para estratégias avançadas de gestão de rebanhos domésticos em Ota, consistentes com práticas contemporâneas observadas em outros sítios Calcolíticos nas regiões da Estremadura e do Alentejo. Além disso, as evidências isotópicas estáveis sugerem que o assentamento muralhado de Ota pode ter participado em redes existentes de troca de animais durante o 3.º milénio a.C. Ao oferecer insights sobre a criação de animais e suas implicações socioeconómicas, este estudo contribui para a compreensão da complexa interação entre ambiente, estratégias de subsistência e organização social no Calcolítico do Oeste da Península Ibérica.